THE CORRELATION BETWEEN READING MOTIVATION AND READING COMPREHENSION OF ELEVETH GRADE STUDENTS OF SMAN 1 SIMPANG KANAN ROKAN HILIR - Ningsih, Sri Wahyu; Novitri, Novitri; Purwanti, Indah Tri (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This present study was aimed to find out whether there was a correlation between reading motivation and reading comprehension of the eleventh grade students of SMAN 1 Simpang Kanan Rokan Hilir. The population was the eleventh grade students of SMAN 1 Simpang Kanan Rokan Hilir. The sample, consisting of 38 students was chosen by using cluster random sampling. The instruments were reading questionnaire and reading comprehension test. Reading motivation questionnaire was used to know the students’ reading motivation while reading comprehension test was used to know the students’ ability in understanding a text. The obtained data were analyzed by using Pearson Product Moment’s Formula. Based on the data analysis, it showed that there was moderate correlation between reading motivation and reading comprehension of the eleventh grade students of SMAN 1 Simpang Kanan Rokan Hilir. The result revealed that the coefficient correlation was higher than the critical value of r-table (0.601 > 0.320). Therefore, it answered the research question that there was a correlation bewtween reading motivation and reading comprehension.Key Words: Correlation, Reading Motivation, Reading Comprehension